STRESS AND DEFORMATION STUDY ON CASTELLATED STEEL BEAM WITH TAPERED SHAPE AND HEXAGONAL OPENINGS - Taufiq Ilham Maulana; Bagus Soebandono; Aris Susanti (Universitas Mercu Buana, 2019)
Castellated steel beam is a beam with a regular section cut into half with a particular pattern and regrouped with welding to increase its height compared to the original. This structure element has been developed in building constructions since many years ago. However, its uniform section along the span will make the modification no longer effective in cantilever structure, unless it has additional adaptation. Therefore, in this study, it is proposed to use a castellated steel beam with a tapered shape to be applied as cantilever structures. A steel beam with IWF section 150x75x5x7 is the primary sample type in this research. Some variations were made such as openings angle for 450 and 500, openings space for 50 mm, 70 mm, and 90 mm, openings diameter for 50 mm, 75 mm, and 100 mm, and span length for 2 m, 2.5 m, 3 m, and 3.5 m. Two open-source software namely FreeCAD and LisaFEA were used to draw solid 3-dimensional samples and to conduct the numerical analysis to determine stress and deformation respectively. From the result, it is known that the smallest stresses and deformations can be achieved by a different angle of openings, openings space, and diameter for each span length.